2004
DOI: 10.1182/blood-2003-10-3428
|View full text |Cite
|
Sign up to set email alerts
|

Impaired platelet responses to thrombin and collagen in AKT-1–deficient mice

Abstract: We investigated the role of Akt-1, one of the major downstream effectors of phosphoinositide 3-kinase (PI3K), in platelet function using mice in which the gene for Akt-1 had been inactivated. Using ex vivo techniques, we showed that Akt-1-deficient mice exhibited impaired platelet aggregation and spreading in response to various agonists. These differences were most apparent in platelets activated with low concentrations of thrombin. Although Akt-1 is not the predominant Akt isoform in mouse platelets, its abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
232
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(254 citation statements)
references
References 28 publications
19
232
0
3
Order By: Relevance
“…PI3K has been observed to promote Akt activation during platelet stimulation [16,25], and two different isoforms of Akt, Akt1/PKBα and Akt2/PKBβ, have been found to play a role in platelet activation [3]. Once phosphorylated, Akt is known to phosphorylate and activate in its turn other proteins, including eNOS [9].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K has been observed to promote Akt activation during platelet stimulation [16,25], and two different isoforms of Akt, Akt1/PKBα and Akt2/PKBβ, have been found to play a role in platelet activation [3]. Once phosphorylated, Akt is known to phosphorylate and activate in its turn other proteins, including eNOS [9].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is interesting to note that endothelial nitric oxide synthase can be activated in endothelial cells by Akt (50), a serine/threonine protein kinase that is a downstream effector of phosphatidylinositol 3-kinase. We and others have shown that phosphatidylinositol 3-kinase and Akt play important roles in platelet secretion and second wave platelet aggregation (12,51,52). Thus, it will be interesting to investigate further whether activation of cGMP/PKG is downstream from the phosphatidylinositol 3-kinase-Akt pathway during platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PI3K and Akt are known to promote platelet secretion and secretion-dependent platelet aggregation (16,20,53,54), and the effects of PI3K and Akt are mediated via the NO-sGC/cGMP-PKG pathway (20,32). In this study, we further show that 1) the SFK inhibitor, PP2, inhibited agonist-induced Akt phosphorylation, indicating that SFK is important in GPCR-mediated activation of the PI3K-Akt signaling pathway; 2) PP2 and Lyn knock-out also inhibited thrombin-and collagen-induced increases in the intracellular cGMP levels in platelets, indicating that SFK is upstream of the NO-cGMP signaling pathway; 3) supplementation of low concentrations of 8-bromo-cGMP corrected the platelet aggregation defect caused by PP2 and Lyn knock-out and partially but significantly reversed the inhibitory effect of PP2 on platelet granule secretion, indicating that SFK (Lyn)-mediated activation of the cGMP signaling pathway plays an important role in the stimulatory effect of SFK (Lyn) on platelet secretion and aggregation; and 4) similar to PP2, the specific sGC inhibitor ODQ inhibited platelet aggregation in response to low dose thrombin (19).…”
Section: Discussionmentioning
confidence: 99%